2003
DOI: 10.1038/sj.onc.1206387
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lung tumorigenesis in chimeric mice indicates the Pulmonary adenoma resistance 2 (Par2) locus to operate in the tumor-initiation stage in a cell-autonomous manner: detection of polymorphisms in the Polı gene as a candidate for Par2

Abstract: The Pulmonary adenoma resistance 2 (Par2) locus of the BALB/cByJ mouse, located within 0.5 cM of chromosome 18, is responsible for reducing the mean multiplicity of urethane-induced lung tumors relative to those in C57BL/ 6J, A/J and C3H/HeJ mice. Thus, BALB/B6-Par2 congenic strain genetically identical to BALB/cByJ except carrying C57BL/6J Par2 alleles develops seven times more tumors than BALB/cByJ. To gain clues for identification of Par2 candidate genes, we analysed lung tumorigenesis in BALB/cByJ2BALB.B6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 21 publications
1
42
1
Order By: Relevance
“…2A, we have identified 10 amino acid-changing polymorphisms and two alternatively spliced exons in Pol between A/J and BALB/cJ mice. Among them, 9 amino acid polymorphisms and 1 alternative splicing variant were consistent with those reported previously (13). The newly observed amino acid changing polymorphism at codon 606 encodes a positively charged arginine (CGA) in BALB/cJ but a neutral Glutamine (CAA) in A/J (Fig.…”
Section: Expression and Nucleotide Polymorphism Analyses Of Genes In supporting
confidence: 90%
See 2 more Smart Citations
“…2A, we have identified 10 amino acid-changing polymorphisms and two alternatively spliced exons in Pol between A/J and BALB/cJ mice. Among them, 9 amino acid polymorphisms and 1 alternative splicing variant were consistent with those reported previously (13). The newly observed amino acid changing polymorphism at codon 606 encodes a positively charged arginine (CGA) in BALB/cJ but a neutral Glutamine (CAA) in A/J (Fig.…”
Section: Expression and Nucleotide Polymorphism Analyses Of Genes In supporting
confidence: 90%
“…Four known genes are located in this region, i.e., StarD6, Pol , Mbd2, and Dcc. Preliminary analysis of the polymorphisms in the Dcc and Pol genes were reported recently (11,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have strongly indicated a genetic linkage between chemical-induced lung tumor formation and Pol deficiency in BALB/cJ and A/J mice (31,32,68). These findings have suggested that the Pol protein may be involved in preventing certain tumors.…”
Section: Role For Pol In Prevention Of Uv-induced Mesenchymal Tumorsmentioning
confidence: 89%
“…Interestingly, the mice counterpart for POLI, Poli, was recently identified as a strong candidate for the Par2 (pulmonary adenoma resistance 2) gene responsible for reducing the mean multiplicity of urethane-induced lung adenoma/adenocarcinoma. 27 POLI/Poli proteins undertake the error-prone translesion DNA synthesis in incorporating deoxynucleotides opposite highly distorting or noninstructional DNA lesions. Thus, interindividual differences in the activity of POLI/ Poli proteins due to polymorphisms might cause the interindividual differences in the probability of mutagenesis in both humans and mice.…”
Section: Discussionmentioning
confidence: 99%